Attitudes, weight stigma and misperceptions of weight loss strategies among patients living with obesity in the Lazio Region, Italy - Colangeli, Luca; Russo, Benedetta; Capristo, Esmeralda; Mariani, Stefania; Tuccinardi, Dario; Manco, Melania; Scipione, Valeria; Parrotta, Maria Eugenia; Capoccia, Danila; Guglielmi, Valeria (Frontiers in Endocrinology, 2024)
Introduction. Patient engagement is essential to achieve long-term goals in obesity management. It is crucial to identify patients' perspectives, misperceptions and unmet educational needs on obesity etiology and treatments, to establish a correct therapeutic alliance between healthcare providers and patients.Methods. Objective: This study, promoted by the regional section of the Italian Obesity Society (SIO Lazio), explores attitudes towards obesity, self-awareness, misperceptions of weight loss strategies, experiences of weight stigma and educational needs of patients living with overweight or obesity. Design and subject: We conducted an anonymous survey among patients who accessed an Obesity Management Centres across the Lazio region of Italy for the first time, from October 2023 to April 2024. Approach: The survey consisted of 27 closed-ended questions grouped into 4 sections: (1) sociodemographic factors and self-reported anthropometric measures; (2) self-awareness and attitudes Conclusions. Despite advancements in obesity research, this study underscores the need to improve patient education and public awareness to optimize the management and treatment of obesity. Addressing misconceptions, stigma, and gaps in knowledge are critical steps towards improving patient outcomes and fostering a supportive healthcare environment.